Solitons in Nuclear Time-Dependent Density Functional Theory - Iwata, Yoritaka (Frontiers in Physics, 2020)
The soliton existence in sub-atomic many-nucleon systems will be discussed. In many nucleon dynamics represented by the nuclear time-dependent density functional formalism, much attention is paid to energy and mass dependence of the soliton existence. In conclusion, the existence of nuclear soliton is clarified if the temperature of nuclear system ranges from 10 to 30 MeV. With respect to the mass dependence 4He and 16O are suggested to be the candidates for the self-bound states exhibiting the property of nuclear soliton.